English as a Medium of Instruction (EMI): A primary school teachers’ and students’ perceptions - Ernawati, Ernawati; Sofendi, Sofendi; Silvhiany, Sary (International Journal of Research in Counseling and Education, 2021)
The English language is becoming a global lingua franca, given its association with critical turns such as globalization, global economy, international communication, and the Internet. Many countries try to develop their countries start from the educational sector and put English as the language needed to learn in schools of many countries such as Indonesia. The use of English was becoming a global phenomenon that English is becoming a language of instruction in schools. The impact of utilizing English suggests that in a few universal academic settings, there is an apace developing inclination for English received as a medium of instruction (EMI). EMI applied in many educational levels started from the University, High School, and even in the early grade, such as Primary School. With the use of EMI in many educational systems, several issues rose related to its use in the classroom. Many of the studies found a lack of English proficiency, both from teachers and students in the use of EMI and several other problems. Related to this issue, the researcher conducted a study. Through a qualitative study in a case study design, the perception of teachers and pupils of a primary school in Palembang was explored and investigated. The participants of this study were the fifth-grade teachers and pupils in Paramount School Palembang. The data were collected by open-ended interviews with 3 Science teachers, 2 Mathematics teachers and 12 pupils in Paramount School Palembang. Thematic analysis was used in analyzing the data, and then the data were coded and classified into categories to form big themes based on the perceptions and information. The data analyzed revealed a consistency between teachers' and pupils' perceptions about EMI use in the classroom. The result mentioned that the teachers and pupils had positive perceptions because of the benefit of using English as a medium of instruction.